2018
DOI: 10.1002/hbm.24243
|View full text |Cite
|
Sign up to set email alerts
|

An efficient and accurate method for robust inter‐dataset brain extraction and comparisons with 9 other methods

Abstract: Brain extraction is an important first step in many magnetic resonance neuroimaging studies. Due to variability in brain morphology and in the appearance of the brain due to differences in scanner acquisition parameters, the development of a generally applicable brain extraction algorithm has proven challenging. Learning-based brain extraction algorithms in particular perform well when the target and training images are sufficiently similar, but often perform worse when this condition is not met. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Moreover, a case‐specific tuning of parameters from these brain extraction algorithms may have allowed to improve their performance to some extent (Iglesias et al, ; Popescu, et al, ). This is particularly the case for BEaST, where a mismatch between source and target domain can result in a significant drop in performance (Eskildsen et al, ; Novosad & Collins, ). Dataset‐specific adaptations are, however, not a practical approach, especially in the context of high‐throughput processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a case‐specific tuning of parameters from these brain extraction algorithms may have allowed to improve their performance to some extent (Iglesias et al, ; Popescu, et al, ). This is particularly the case for BEaST, where a mismatch between source and target domain can result in a significant drop in performance (Eskildsen et al, ; Novosad & Collins, ). Dataset‐specific adaptations are, however, not a practical approach, especially in the context of high‐throughput processing.…”
Section: Discussionmentioning
confidence: 99%
“…For every test, we reported the absolute value of the Z-statistics [abs(Z)], the Bonferroni-adjusted p-value and the effect size [r] (with r values >.1 corresponding to a small effect, .3 to a medium effect, and .5 to a large effect size; Cohen, 1988 tuning of parameters from these brain extraction algorithms may have allowed to improve their performance to some extent (Iglesias et al, 2011;Popescu, et al, 2012). This is particularly the case for BEaST, where a mismatch between source and target domain can result in a significant drop in performance (Eskildsen et al, 2012;Novosad & Collins, 2018). Dataset-specific adaptations are, however, not a practical approach, especially in the context of high-throughput processing.…”
Section: Discussionmentioning
confidence: 99%
“…Some such methods have attempted to learn complex mappings between image features and labels using traditional machine-learning based classifiers (e.g., support vector machines (Boser, Guyon, & Vapnik, 1992) and random forests (Breiman, 2001)) combined with handcrafted feature sets (Morra et al, 2010;Zikic et al, 2012), while others have found success transferring labels using a combination of linear or nonlinear image registration with local and/or nonlocal label fusion (so-called "multiatlas segmentation" methods (Coupé et al, 2011, Heckemann, Hajnal, Aljabar, Rueckert, & Hammers, 2006, Iglesias & Sabuncu, 2015). Indeed, many state-of-the-art results (e.g., hippocampus segmentation (Zandifar, Fonov, Coupé, Pruessner, & Collins, 2017) and brain extraction (Novosad & Collins, 2018) exploit a complementary combination of both multiatlas segmentation and machine-learning methods (e.g., error correction (EC) (Wang et al, 2011)).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many state-of-the-art results (e.g. hippocampus segmentation (Zandifar et al, 2017) and brain extraction (Novosad and Collins, 2018)) exploit a complementary combination of both multi-atlas segmentation and machine-learning methods (e.g. error correction (Wang et al, 2011)), though the computational time required for segmentation is usually correspondingly greater.…”
Section: Introductionmentioning
confidence: 99%